Pengaruh Pendapatan Asli Daerah, Dana alokasi Umum Dan Dana Alokasi Khusus Terhadap Indeks Pembangunan ManusiaStudi kasus pada Kabupaten Kota di Jawa Tengah Periode 2012-2014 - Amalia, Risha, Dr. Erma Setiawati, MM.,CA (2016)
This research aims to find out and analyze the influence of the original Revenue areas, General allocation Funds and Special Funds Allocation against the human development index district/city of Central Java province in the period of 2012 - 2014. Type of this research is quantitative research. The sample used in this study was 35 district/municipality which consists of 6 towns and 29 regencies in Central Java province. This study uses secondary data in the form of Government BUDGETS-realization Report district/city of Central Java province in the period of 2012 - 2014 and the human development index. Data analysis using a classic assumption test, test hypotheses and coefficients of determination. The results showed that the original Regional Revenue (PAD) and the General Allocation Fund (DAU) has an influence on the human development index, while the Special Allocation Fund (DAK) has no effect against the human development index. Key Words : Native Revenue (PAD), General Allocation Funds (DAU), Special Allocation Fund (DAK), The Human Development Index (Hdi)